Burnout Among Saudi Radiographers - Alsultan KD; Gameraddin M; Talal S; Alhujaili MO; Alshoabi SA; Salih S; Abdelmalik BH; Alhazmi FH; Gareeballah A; Aman AM (Dove Medical Press, 2024)
Kamal Dahan Alsultan,1 Moawia Gameraddin,1,2 Sultan Talal,1 Mohammad Osama Alhujaili,1 Sultan Abdulwadoud Alshoabi,1 Suliman Salih,3 Bushra HA Abdelmalik,4 Fahad H Alhazmi,1 Awadia Gareeballah,1 Abdulmannan Mohamed Aman5 1Department of Diagnostic Radiology Technology, College of Applied Medical Sciences, Taibah University, Al-Madinah, Saudi Arabia; 2Department of Diagnostic Radiology, Faculty of Radiological Sciences and Medical Imaging, Alzaiem Alazhari University, Khartoum, Sudan; 3Radiology and Medical Imaging Department, Fatima College of Health Sciences, Abu Dhabi, United Arab Emirates; 4Diagnostic Radiology Department, College of Applied Medical Sciences, University of Ha'il, Ha'il, Saudi Arabia; 5Medical Centre, faculty of Medicine, Taibah University, Al-Madinah, Saudi ArabiaCorrespondence: Moawia Gameraddin, Department of Diagnostic Radiology Technology, College of Applied Medical Sciences, Taibah University, Al-Madinah, Saudi Arabia, Email gameraldinm@gmail.comIntroduction: Burnout research is limited in Saudi Arabia, particularly among radiographers. Burnout among Saudi radiographers may have a negative impact on the services offered.Objective: This study aims to assess the burnout among radiographers in Medina hospitals.Materials and Methods: This quantitative cross-sectional study included 104 radiographers from government and private Medina hospitals. The Maslach Burnout Inventory-Human Services Survey for Medical Personnel, which consists of 22 questions, was used to measure the burnout level. The data were evaluated descriptively using the Statistical Package for the Social Sciences (version 25), and independent t-tests and analysis of variance were applied to assess group differences and linear regression analysis to evaluate associations between the burnout level and sociodemographic variables (ie sex, age, experience, and department).Results: The emotional exhaustion (EE) and depersonalization (DP) scores were moderate, while the personal accomplishment (PA) score was high, with total scores of 23.53 (9.32), 7.29 (5.95), and 29.70 (1.35), respectively. The DP score was influenced by the participants' experience. Specifically, an experience of 1- 5 years yielded a substantially higher burnout score than did an experience of > 10 years (p> 0.05). Conversely, sex, age, and department did not affect the DP score (p< 0.05). Similarly, the EE and PA scores were not influenced by sex, age, experience, or department (p< 0.05).Conclusion: Burnout is prevalent among radiographers in Medina hospitals in Saudi Arabia. The EE and DP scores are moderate, while the PA score is high, indicating a suitable work environment. Policymakers should take the required steps to identify the variables contributing to employee burnout and enhance the work environment.Keywords: burnout, radiographers, emotional exhaustion, EE, depersonalization, DP, personal accomplishment, PA